Genomic profiles and prognostic biomarkers of resectable lung adenocarcinoma with a micropapillary component - Zhu, Jiafu; Sun, Xinhai; Huang, Jiangshan; Lin, Wenwei; Zhan, Yanyan; Yan, Junrong; Xu, Yang; Wu, Long; Lian, Yuane; Zhang, Zhenyang; Lin, Jiangbo (Frontiers in Oncology, 2025)
BackgroundLung adenocarcinoma with a micropapillary component (LMPC) is an aggressive histologic subtype of lung cancer characterized by unique pathological features and poor prognosis. While previous studies have identified driver mutations in LMPC, its comprehensive molecular profile and prognosis-related biomarkers in the Chinese population remain poorly understood.MethodsWe conducted a retrospective study of 54 stage I-III LMPC patients who underwent complete resection. Tumor samples from these patients were analyzed using broad-panel next-generation sequencing of 425 cancer-related genes. We explored the associations among clinicopathologic factors, genomic characteristics, and post-operative recurrence risk.ResultsCompared to a reference cohort of 113 LADC patients, LMPC exhibited a distinct genetic profile, with a greater diversity of targetable mutations, an increased number of oncogenic pathway alterations (NPA), and more oncogenic pathway-related alterations. The mutation frequencies of ERBB4 (11.1% vs. 1.8%, P=0.015), BRAF (9.3% vs. 1.8%, P=0.037), PIK3CA (14.8% vs. 4.4%, P=0.029), RPTOR (P=0.033), and NOTCH2 (P=0.033) were significantly higher in LMPC. Additionally, LMPC patients had significantly more alterations in three oncogenic pathways (PI3K, Wnt, and TGF-β) and a significantly increased NPA (P<0.001). In stage II-III LMPC patients, SMARCA4 mutations (13.9 months vs. not reached (NR), P=0.013) and alterations in the SWI/SNF (16.3 months vs. NR, P=0.003) and Nrf2 (17.0 months vs. NR, P=0.046) pathways were significantly associated with higher postoperative recurrence risk. Furthermore, tumor mutation burden (TMB) was significantly correlated with postoperative disease-free survival (DFS), with patients having low TMB showing prolonged median DFS compared to those with high TMB (NR vs. 16.8 months, P=0.021).ConclusionOur study elucidates the unique genetic landscape of Chinese resectable LMPC patients and highlights high TMB and mutations in SMARCA4, SWI/SNF, and Nrf2 pathways as potential prognostic indicators in stage II-III disease. As these factors were not confirmed in multivariate models, they should be validated in larger, multi-center cohorts to guide future risk stratification and treatment decisions.